Lattice-based J integral for a steadily moving dislocation. (March 2021) - Kim, Hokun; Kim, Soon; Kim, Sung Youb
Abstract: According to continuum theory and the conservation theorem, the J integral represents the net translational force acting on a defect and, specifically, it is equivalent to the Peach–Koehler force for dislocation. In this study, we newly derive the J integral to quantify driving force on a uniformly moving dislocation with considering its core-induced dynamic behaviors. Using both molecular dynamics simulation and lattice dynamics theory based on atomic chain model, we prove that radiation drag and self-stress asymmetry during the dislocation motion, which are generated by lattice discreteness, make the newly derived J integral depend on the distance from the dislocation core, which is lumped into resistance to the dislocation motion. Finally, we show that the J integral converges to the Peach–Koehler force as the resistance term disappears for a stationary dislocation. Highlights: The J integral is newly derived with considering the dislocation core-induced dynamic behaviors. A discreteness of lattice system induces phonon radiation from the dislocation core. A gliding dislocation induces asymmetry in its self-stress field and breaks the path-independence of the J integral. Phonon radiation and dislocation self-stress asymmetry are lumped into resistance to the dislocation motion. Using the lattice dynamics theory, the J integral is analytically derived with considering the lattice discreteness.